The Bible and cinema : an introduction - Reinhartz, Adele (London Routledge, 2022)
"Bible and Cinema: An Introduction is a comprehensive examination of how the Bible has been used and represented in mainstream cinema to develop their plots, characters, and themes. The book considers two general types of films: Bible movies that retell biblical stories, such as the Exodus and the life of Jesus, and Bible-related movies that make use of biblical books, stories, verses, and figures, and Bibles themselves to tell non-biblical, often fictional, narratives. Topics covered include: the contribution of Bible and Bible-related movies to the history of the Bible's reception; the ways that filmmakers make use of scripture to address and reflect their own time and place; the Bible as a vehicle through which films can address social and political issues, reflect human experiences and emotions, explore existential issues such as evil and death, and express themes such as destruction and redemption; the role of the Bible as a source of ethics and morality, and how this role is both perpetuated and undermined in a range of contemporary Hollywood films; Film as a medium for experiences of transcendence, and the role of the Bible in creating such experiences. This thoroughly updated second edition includes insightful analysis of films such as Noah, Gods and Men, Mary Magdalene and The Shawshank Redemption, paying attention to visual and aural elements as well as plot, character, and dialogue. This book also includes pedagogical resources including discussions of film theory, as well as key words and discussion questions. Teachers, students, and anyone interested in the intersection of Bible and cinema will find this an invaluable guide to a growing field"--
"As it has been written" : the Old Testament epics -- "I have seen the Lord" : Jesus on the silver screen -- "Make disciples of all nations" : swords, sandals, and Christianity -- "What would Jesus do?" Epic and analogy -- "Make them known to your children" : the Old Testament in modern guise -- "One like a son of man" : Christ-figure films -- "The devil quotes scripture" : movies and morals -- "In that future day" : worlds destroyed and restored -- "My heart is glad, and my soul rejoices:" cinema and transcendence.
Includes bibliographical references and index.
Keywords: Motion pictures